Acute exacerbation of idiopathic interstitial pneumonias related to chemotherapy for lung cancer: nationwide surveillance in Japan. Issue 2 (26th May 2020) - Minegishi, Yuji; Gemma, Akihiko; Homma, Sakae; Kishi, Kazuma; Azuma, Arata; Ogura, Takashi; Hamada, Naoki; Taniguchi, Hiroyuki; Hattori, Noboru; Nishioka, Yasuhiko; Tanizawa, Kiminobu; Johkoh, Takeshi; et al.
Background: Chemotherapy-induced acute exacerbation (AEx) of idiopathic interstitial pneumonias (IIPs) seriously compromises the success of treatment of Japanese lung cancer patients. Here, we conducted a nationwide surveillance to clarify the risk of AEx and compare it with the survival benefit of chemotherapy for this population. Methods: Advanced nonsmall cell lung cancer (NSCLC) or small cell lung cancer (SCLC) patients with IIPs were retrospectively analysed. For the surveillance of first-line chemotherapy in 2009, we gathered clinical data from 396 patients who received chemotherapy at 19 institutions between January 1990 and July 2009. In a consecutive retrospective study in 2012, we analysed data from 278 patients from 17 institutions who received second-line chemotherapy between April 2002 and March 2012. Results: Of the 396 patients analysed, 13.1% developed chemotherapy-related AEx. Combination chemotherapies of carboplatin plus paclitaxel (CP) or carboplatin plus etoposide (CE) were frequently used as first-line treatments. The lowest incidence of AEx was 3.7% in CE, followed by 8.6% in CP. In the retrospective study, 16.2% of the 278 patients developed a second-line chemotherapy-related AEx. The overall response rate by second-line chemotherapy was 7.4% in NSCLC and 25.7% in SCLC. The median overall survival from second-line and first-line chemotherapy was 8.0 and 14.3 months in NSCLC, and 8.7 and 16.0 months in SCLC, respectively. Conclusion: Combination chemotherapies consisting of CP or CE are candidates for standard first-line treatments for patients with advanced lung cancer accompanied by IIP. Second-line chemotherapy should be considered for patients remaining fit enough to receive it. The Japanese are at high risk of acute exacerbation of IPF. Therefore, chemotherapy for Japanese lung cancer patients with IIPs is challenging. However, appropriate chemotherapy may give a survival benefit, despite the risk of acute deterioration of IIPs. http://bit.ly/3cROaCy